Study on the structural evolution of semi-chars and their solvent extracted materials during pyrolysis process of a Chinese low-rank coal. (15th February 2018) - Zhang, Liangping; Hu, Song; Xu, Kai; Jiang, Long; Wang, Yi; Su, Sheng; Xiao, Yiming; Shan, Lianying; Shen, Wenzhong; Li, Huafei; Chen, Gang; Xiang, Jun
Graphical abstract: Proposed conversion process of the chemical structure of Shenfu low-rank coal during low-temperature pyrolysis, especially considering the solvent extracted metaplast materials (SEMMs) in semi-chars. Highlights: 51.8% of solvent extracted materials in semi-char disappeared in initial 1 min. Aromatic structures with 1–2 rings were produced and turned into oil or asphaltene. Active aromatic structures with ≥4 rings mainly decomposed in initial 5 min. A coal pyrolytic conversion process considering metaplast materials was proposed. Abstract: The structural evolution of coal during pyrolysis process has been studied for a long time but remains unclear, mainly due to the extraordinary complexity of coal structure. The present study aimed to further identify the chemical structural evolution of different parts in the semi-chars obtained by low-temperature pyrolysis of a Chinese low-rank coal (Shenfu coal). Semi-chars and their solvent extracted materials (oil, resin, asphaltene and preasphaltene) were analyzed by 13 C nuclear magnetic resonance (NMR) mass spectrometry, diffuse reflectance Fourier transform-infrared spectroscopy (DRIFTs) and ultraviolet (UV) fluorescence spectroscopy, separately. The results showed that 23.8% weight loss occurred during the whole pyrolysis process at 435 °C and half of the weight loss was achieved in the initial five minutes. By contrast, amount of the extracts in semi-chars (solvent extracted metaplast materials) decreased more dramatically in the initial stage of the pyrolysis, and 51.8% of the extracts disappeared in the initial one minute. Oil and preasphaltene showed higher thermal sensitivity than asphaltene and resin. Considerable content of metaplast materials with 1–2 rings (especially in oil and/or asphaltene) were produced along with the pyrolysis process. Condensed aromatic structures in semi-chars were relatively stable and mainly decomposed in the initial stage of pyrolysis which could be attributed to the dramatically decomposition of some active aromatic structures with ≥ 4 rings (especially the components in extracts such as preasphaltene). The results provided a new insight into the structural evolution of coal during low-temperature pyrolysis process, which specially considered the detailed information of the solvent extractable metaplast materials in semi-chars.